The Colorado River Delta and California's Central Valley are critical regions for many migrating North American landbirds. Issue 1 (26th January 2021) - DeLuca, William V; Meehan, Tim; Seavy, Nat; Jones, Andrea; Pitt, Jennifer; Deppe, Jill L; Wilsey, Chad B
Abstract: Migration is an important component of some species full annual cycle. California's Central Valley and the Colorado River Delta provide important riparian and wetland habitats for migrating waterbirds in the arid west of North America, but little is known about whether these locations are important at the population level to migrating landbirds. We used eBird Status and Trends abundance data to quantify the importance of the Central Valley and Colorado River Delta to landbirds by estimating the proportion of the breeding population of 112 species that use each site during migration. We found that 17 million landbirds use the Colorado River Delta in the spring and 14 million in the fall. Across 4 study regions in the Central Valley, up to 65 million landbirds migrate through in the spring and up to 48 million in the fall. In the spring and fall, respectively, up to 37 and up to 30 species had at least 1% of their continental population migrate through the study regions. We also quantified the spatial concentration of each species across latitudinal transects to determine the extent to which study regions were acting as migratory bottlenecks. Landbird abundances were spatially concentrated in study regions 29.4% of all migration weeks, indicating that each study region acts as a migratory bottleneck. This application of eBird data is a powerful approach to quantifying the importance of sites to migrating birds. Our results provide evidence of population-level importance of the Central Valley and Colorado River Delta for many migratory landbirds. Lay Summary: Migratory birds are declining throughout North America, and we must identify places birds need during migration so they can safely move between breeding and winter locations. The Colorado River Delta and the Central Valley are known as important landscapes for wildlife, but their importance to migrating landbirds is not well known. We used eBird data to measure the importance of the Colorado River Delta and California's Central Valley to birds that migrate through western North America. Many species have substantial portions of their populations that depend on these locations during migration. Conservation of the Colorado River Delta and Central Valley are important for the entire populations of many breeding landbird species of North America. Graphical Abstract: